Recent Advances and Challenges in Metal Halide Perovskite Quantum Dot-Embedded Hydrogels for Biomedical Application - Junyi Yu; Chengran Zhang; Lijun Kong; Zhengtao Deng (Molecules)
Metal halide perovskite quantum dots (MHP QDs), as a kind of fluorescent material, have attracted much attention due to their excellent photoluminescence (PL) quantum yield (QY), narrow full width at half maximum (FWHM), broad absorption, and tunable emission wavelength. However, the instability and biological incompatibility of MHP QDs greatly hinder their application in the field of biomedicine. Hydrogels are three-dimensional polymer networks that are widely used in biomedicine because of their high transparency and excellent biocompatibility. This review not only introduces the latest research progress in improving the mechanical and optical properties of hydrogels/MHP QDs but also combines it with the existing methods for enhancing the stability of MHP QDs in hydrogels, aiming to provide new ideas for researchers in material selection and methods for constructing MHP QD-embedded hydrogels. Finally, their application prospects and future challenges are introduced.